Gray's anatomy for students - Drake, Richard L.; Vogl, Wayne; Mitchell, Adam W. M.; Gray, Henry (Philadelphia : Elsevier/Churchill Livingstone, 2005)
"Written by a team of authors with a wealth of diverse teaching and clinical experience, Gray's Anatomy for Students is carefully crafted to concisely cover the material taught in contemporary anatomy courses. An international advisory board, comprised of more than 100 anatomy instructors, ensures that the book is accurate, up to date, and easy to use." "More than 1,000 original and innovative illustrations describe and explain anatomical features with clarity. Consistent use of color throughout makes body structures easy to locate and remember from illustration to illustration. In addition, over 300 photographs and radiological images depict surface anatomy and common clinical applications of anatomical knowledge."--BOOK JACKET.
Includes index.
Keywords: Human anatomy; Anatomy